Classification of Malware using Machine learning and Deep learning Techniques - Dr.Khyati Rami ,Prashant Halvadiya , Mayank Devani (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The threats impose by the cyber-attacks due to malicious software (malware) have beenincreasing drastically with the evolution of information technology. Since people use webapplications on a daily basis these malware attacks have become challenging